Performance evaluation of music and minimum norm Eigenvector Algorithms in resolving noisy multiexponential signals - Jibia, Abdussamad Umar; Salami, Momoh Jimoh Eyiomika (World Academy of Science, Engineering and Technology (W A S E T), 2007)
Abstract—Eigenvector methods are gaining increasing acceptance in the area of spectrum estimation. This paper presents a successful attempt at testing and evaluating the performance of two of the most popular types of subspace techniques in determining the parameters of multiexponential signals with real decay constants buried in noise. In particular, MUSIC (Multiple Signal Classification) and minimum-norm techniques are examined. It is shown that these methods perform almost equally well on multiexponential signals with MUSIC displaying better defined peaks